Functionalization of Non‐activated CH Bonds of Alkanes: An Effective and Recyclable Catalytic System Based on Fluorinated Silver Catalysts and Solvents. Issue 4 (29th November 2012) - Fuentes, M. Ángeles; Muñoz, Bianca K.; Jacob, Kane; Vendier, Laure; Caballero, Ana; Etienne, Michel; Pérez, Pedro J.
Abstract The complexes Fn‐Tp 4Bo, 3R f<inline-graphic xlink:href="ark:/27927/pgg1p9fv5m2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Ag(L) (Fn‐Tp 4Bo, 3R f<inline-graphic xlink:href="ark:/27927/pgg1p9fv5jz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />=a perfluorinated hydrotris(indazolyl) borate ligand; L=acetone or tetrahydrofuran) efficiently catalyze the functionalization of non‐activated alkanes such as hexane, 2, 3‐dimethylbutane, or 2‐methylpentane by insertion of CHCO2Et units (from N2CHCO2Et, ethyl diazoacetate, EDA) into their CH bonds. The reactions are quantitative (EDA‐based), with no byproducts derived from diazo coupling being formed. In the case of hexane, the functionalization of the methyl CH bonds has been achieved with the highest regioselectivity known to date with this diazo compound. This catalytic system also operates under biphasic conditions by using fluorous solvents such as Fomblin or perfluorophenanthrene. Several cycles of catalyst recovery and reuse have been performed, with identical chemo‐ and regioselectivities.